THE PROCESSING AND PACKAGING OF PASTRIES AND KENONG COOKIES TO IMPROVE THE SELLING VALUE AND UNIQUENESS OF LOCAL PRODUCTS IN BENDUNG VILLAGE, BENDUNG DISTRICT, KASEMEN SUB-DISTRICT, SERANG - Tia Fitria Saumi; Sri Sukmawati; Diana Romdhoningsih; Mahpudoh Mahpudoh; Irma Nurmala Dewi (Yayasan Education and Social Center, 2022)
Community Service on Training on Processing and Packaging Techniques of Pastries and Kenong in Bendung District, Kasemen Sub-district of Serang, with the target of MSME actors, Pastries and Kenong, Bendung Village, the purpose of this community service activity is to provide training on the processing and packaging of pastries and kenong in the Bendung village, Kasemen district, Serang. The technique used in this service activity is lecturing the participants on processing and packaging techniques for cookies and kenong. Namely, SME players can be directly involved in practising and creatively processing and packaging products attractively to become food products with an appealing appearance and flavour. And it is worthwhile to sell it so that it can bring in additional money for the family and potentially grow into a successful business. So while it's encouraging that 60% of training goals achieve for the training, the remaining 40% still need to be followed up with assistance before the next Community Service can complete